Improving the Validity of Mixed and Multi-Methods through Triangulation in New Sports Management Research - Sajjad Pashaie; Mohammad Abbaszadeh; Fatemeh Abdavi; Hamed Golmohammadi (Research in Sport Management and Marketing)
Purpose: The purpose of this research is to improve the validity of mixed and multi-methods through triangulation in sports management research.Methods: In terms of the research design, the current research is a new method research combining several quantitative and qualitative methods and developing tools in mixed and multi-methods, and triangulation and, is evaluation research in terms of practical purpose and orientation.Results: Usually, mixed methods are used to identify the underlying categories of the studied phenomenon, then, in the quantitative phase, a pattern is designed based on the identified categories. Multimethod research is an attempt to combine research methods to address a particular research problem. Multi-methods promise new insights and perspectives in the understanding of phenomena in sports management research. In the mixed method, to a certain extent, the limitation of the selection is proposed methodologically; A limitation that is somewhat seen with multi-methods. Not only does triangulation have no such limitation, but it is broader than the two cases mentioned as it acts as a tool kit for researchers to help understand and explain the subject under study.Conclusion: Therefore, from this point of view, triangulation is more comprehensive than the two methods mentioned, and in the period of late modernity and postmodernity, which emphasizes the new pragmatism, triangulation seems to have a wide range of applications.